Analisis Kesalahan Penggunaan Afiks pada Karangan Siswa Kelas VII SMP Negeri 1 Sambi - Arum, Tiara Puspita; , Drs. Yakub Nasucha, M.Hum (2016)
This research has goals: 1) to explain the mistakes of affixes form from student's essay in class VII SMP N 1 Sambi. This research is using descriptive method with student's essay class VII. This descriptive method is using qualitative research in used. The technique of data collection in this research is using see written. The method which is used to analyze this research is using agih method. The data analysis which is used show that in the student's essay, there much mistakes on affixes, such as: prefixes me-, prefixes ber-, prefixes di-, prefixes ke-, prefixes se-, prefixes ter-, suffixes -i, suffixes -kan, suffixes -nya, conffixes ke-an, infixes -el-, -em-, and -er-. The much mistakes which is used in the student's essay class VII SMP N 1 Sambi is prefixes ber-. Key word: afixs, arrangement.